Right hemisphere brain lateralization for knee proprioception among right-limb dominant individuals - Strong, Andrew; Grip, Helena; Arumugam, Ashokan; Boraxbekk, Carl-Johan; Selling, Jonas; Häger, Charlotte K. (Frontiers in Human Neuroscience, 2023)
Studies indicate that brain response during proprioceptive tasks predominates in the right hemisphere. A right hemisphere lateralization for proprioception may help to explain findings that right-limb dominant individuals perform position matching tasks better with the non-dominant left side. Evidence for proprioception-related brain response and side preference is, however, limited and based mainly on studies of the upper limbs. Establishing brain response associated with proprioceptive acuity for the lower limbs in asymptomatic individuals could be useful for understanding the influence of neurological pathologies on proprioception and locomotion. We assessed brain response during an active unilateral knee joint position sense (JPS) test for both legs of 19 right-limb dominant asymptomatic individuals (females/males = 12/7; mean ± SD age = 27.1 ± 4.6 years). Functional magnetic resonance imaging (fMRI) mapped brain response and simultaneous motion capture provided real-time instructions based on kinematics, accurate JPS errors and facilitated extraction of only relevant brain images. Significantly greater absolute (but not constant nor variable) errors were seen for the dominant right knee (5.22° ± 2.02°) compared with the non-dominant left knee (4.39° ± 1.79°) (P = 0.02). When limbs were pooled for analysis, significantly greater responses were observed mainly in the right hemisphere for, e.g., the precentral gyrus and insula compared with a similar movement without position matching. Significant response was also observed in the left hemisphere for the inferior frontal gyrus pars triangularis. When limbs were assessed independently, common response was observed in the right precentral gyrus and superior frontal gyrus. For the right leg, additional response was found in the right middle frontal gyrus. For the left leg, additional response was observed in the right rolandic operculum. Significant positive correlations were found between mean JPS absolute errors for the right knee and simultaneous brain response in the right supramarginal gyrus (r = 0.464, P = 0.040). Our findings support a general right brain hemisphere lateralization for proprioception (knee JPS) of the lower limbs regardless of which limb is active. Better proprioceptive acuity for the non-dominant left compared with the dominant right knee indicates that right hemisphere lateralization may have meaningful implications for motor control.